The cuneiform uranology texts drawing the constellations - Beaulieu, Paul-Alain 1955-; Frahm, Eckart 1967-; Horowitz, Wayne 1957-; Steele, John M. (Transactions of the American Philosophical Society, 2018)
The cuneiform uranology texts : drawing the constellations, presents a newly recovered group of cuneiform texts from first millennium Babylonia and Assyria that provide prose descriptions of the drawing of Mesopotamian constellations...Chapter 1